Визначення множини законів розподілу ймовірності реалізації загрози безпеці інформації від величини збитків - Мохор, В.В.; Цуркан, В.В. (Моделювання та інформаційні технології, 2010)
The problems of evaluating the probability of information security threats. To
overcome them suggested to identify a set of distribution value of losses due to
information security threats.